1988
DOI: 10.1002/jbm.820220304
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate‐coated porous titanium implants for enhanced skeletal fixation

Abstract: Porous titanium fiber implants for cementless skeletal fixation by bone ingrowth were treated with a calcium phosphate coating applied by a plasma flame-spray technique. In a paired experiment, treated and control implants were inserted in the humeri and olecranons of 36 adult dogs for periods of 1, 2, 4, and 6 weeks. After the animals were sacrificed, a biomechanical evaluation of the strength of skeletal fixation of the implants and a histologic evaluation of bone ingrowth was done. The mean shear strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(59 citation statements)
references
References 32 publications
3
54
2
Order By: Relevance
“…Geesink et al (1987) used uncoated smooth titanium implants as controls and Thomas et al (1987) used macroscopic grooved-configuration implants without porouscoating. In contrast, the control implants used by Rivero et al (1988) consisted of fiber-metal porous surfaces, which presumably may be considered similar to the porous plasma-sprayed controls used in the present study in terms of anchorage capacity. Using porous-surfaced controls instead of smoothsurfaced controls, skeletal fixation is increased, which again increases the demands on the osteoconductive effect of the relatively smooth surfaced hydroxyapatite implant; the opposite is true for smooth-surfaced controls (Skalak 1983, Carlsson et al 1988b, Thomas and Cook 1985.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Geesink et al (1987) used uncoated smooth titanium implants as controls and Thomas et al (1987) used macroscopic grooved-configuration implants without porouscoating. In contrast, the control implants used by Rivero et al (1988) consisted of fiber-metal porous surfaces, which presumably may be considered similar to the porous plasma-sprayed controls used in the present study in terms of anchorage capacity. Using porous-surfaced controls instead of smoothsurfaced controls, skeletal fixation is increased, which again increases the demands on the osteoconductive effect of the relatively smooth surfaced hydroxyapatite implant; the opposite is true for smooth-surfaced controls (Skalak 1983, Carlsson et al 1988b, Thomas and Cook 1985.…”
Section: Discussioncontrasting
confidence: 41%
“…Using similar slight press fit (0.05 undersized holes) for insertion, Cook et al (1988) found no increased anchorage of HAcoated transcortical implants compared with porouscoated Ti-alloy implants. Rivero et al (1988) used a tight pressfit (drill hole 9 mm, implant 10 mm) and found only 24 percent increased fixption of intramedullary implants after 4 weeks and no effect after observation periods of 1, 2, and 6 weeks. Our findings correspond well with Rivero et al (1988) in that no mechanical effect of HA was obtained in the implants in tight press fit (0.4-mm undersized holes), whereas a twofold increased fixation was attained in the gap situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem may be overcome by modifying the implant/bone interface for improved osseous integration. Improved osseous integration may be obtained by the use of hydroxyapatite (HAp), b-tri calcium phosphate (b-TCP) and their composite coatings as nominally HAp to enhance the osteoconductivity of metallic implant (Thomas et al, 1987;Filiaggi, et al, 1991;Rivero et al, 1988). These coatings have been shown to promote osseointegration by stimulating bone growth onto the surface (Dey et al, 2011).…”
Section: Bioglass As Coating Of Implantsmentioning
confidence: 99%
“…It has been shown that at 2 weeks, the strength of fixation to this material begins to increase. 30 This may explain why there is such an increase in ALP attachment in TCP as we get closer to 2 weeks.…”
mentioning
confidence: 98%